Study on city composite wastewater treatment by SBR process - LONG Yan; LAO Shan-gen; LIU Xin-wen; FU Wen-jing; SHEN Dong-sheng (浙江大学学报. 农业与生命科学版)
In this paper, the feasibility of treating composite wastewater by Sequencing Batch Reactor (SBR) was studied. The results showed that aeration time influenced the removal efficiency and sludge activity and 10-hour was the optimum duration of aeration for wastewater treatment. When COD in the influent amounted to 430-660 mg/L and NH4+-N was 16.9-21.5 mg/L, COD removal rate reached 90% and COD and NH4+-N in the effluent was, respectively, below 80 mg/L and 14 mg/L.